2009
DOI: 10.1108/14777830910939453
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of construction details as indicators of the environmental impact of materials used on the “skin” in Greek cities

Abstract: Purpose -Construction materials mostly affect the environment during the first stages of their life cycle. Their placement during the construction stage is of equal importance as it affects their environmental impact during the stage of use and the final stage of demolition and rejection. The purpose of this paper is to analyse the environmental impact of different construction details, which are typically used for different city surfaces in Greece. Design/methodology/approach -The analysis of the environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Previous researchers have generally agreed that the planning and design stages in a construction project lifecycle are critical in determining the overall impact on the environment (Mircea et al, 2010;Gangolells et al, 2011;Huang et al, 2013;Harb et al, 2018). Bougiatioti et al (2009) suggested that it is within the initial stages of a lifecycle where the environment endures the most significant negative impact resulting from raw material extraction, manufacturing and production, and forms of transportation. Marsh (2017, p. 81) noted Denmark's policy initiative where "construction professionals are now required to integrate environmental, economic and social responsibility in the earliest phases in the procurement process".…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Previous researchers have generally agreed that the planning and design stages in a construction project lifecycle are critical in determining the overall impact on the environment (Mircea et al, 2010;Gangolells et al, 2011;Huang et al, 2013;Harb et al, 2018). Bougiatioti et al (2009) suggested that it is within the initial stages of a lifecycle where the environment endures the most significant negative impact resulting from raw material extraction, manufacturing and production, and forms of transportation. Marsh (2017, p. 81) noted Denmark's policy initiative where "construction professionals are now required to integrate environmental, economic and social responsibility in the earliest phases in the procurement process".…”
Section: Related Literaturementioning
confidence: 99%
“…Marsh (2017, p. 81) noted Denmark's policy initiative where “construction professionals are now required to integrate environmental, economic and social responsibility in the earliest phases in the procurement process”. Additionally, the secondary effects on the environment are defined by the materials used during construction, future demolition and material rejection, where significant damage to the environment occurs (Bougiatioti et al. , 2009; Huang et al.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation